2018
DOI: 10.1016/j.rbmo.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of male body mass index on assisted reproduction treatment outcome: an updated systematic review and meta-analysis

Abstract: Men with a body mass index (BMI) of 30 or over are more likely to have reduced fertility and fecundity rates. This systematic review and meta-analysis evaluated the effect of male BMI on IVF and intracytoplasmic sperm injection (ICSI) outcome. An electronic search for published literature was conducted in MEDLINE and EMBASE between 1966 and November 2016. Outcome measures were clinical pregnancy rates (CPR) and live birth rates (LBR) per IVF or ICSI cycle. Eleven studies were identified, including 14,372 cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 35 publications
(147 reference statements)
3
46
1
Order By: Relevance
“…In the present study, the ages of females in the H group and L group were similar, excluding the influence of female age for further analysis in the present study. In addition to age, the factors that have been reported to potentially affect the quality of eggs or embryos were similar in the two groups, including BMI of the female or male, age of the male and DFI of semen [26][27][28][29] . Furthermore, the percentage of IVF cycles, primary infertility and infertility duration were comparable between the two groups.…”
Section: Discussionmentioning
confidence: 88%
“…In the present study, the ages of females in the H group and L group were similar, excluding the influence of female age for further analysis in the present study. In addition to age, the factors that have been reported to potentially affect the quality of eggs or embryos were similar in the two groups, including BMI of the female or male, age of the male and DFI of semen [26][27][28][29] . Furthermore, the percentage of IVF cycles, primary infertility and infertility duration were comparable between the two groups.…”
Section: Discussionmentioning
confidence: 88%
“…Two recent meta‐analyses have linked human male obesity to reduced rates of clinical pregnancy and live births following ART, while a third found no evidence for a relationship between male BMI and treatment outcomes of ART . Negative effects of male obesity on embryo development have been detected in both human ART cohort studies and animal high‐fat diet studies, indicating that sperm can transmit detrimental factors to offspring that impair development .…”
Section: Discussionmentioning
confidence: 99%
“…For example, some studies find reduced embryo development and clinical pregnancy rates following assisted reproductive treatments (ART) with sperm from males with a BMI greater than 25, but other studies have found no evidence that male BMI influences post fertilization ART outcomes or pregnancy and perinatal outcomes . Moreover, two recent meta‐analyses concluded that rates of clinical pregnancy and live births following ART are reduced when the male is overweight or obese, while another meta‐analysis concluded that increased male BMI does not influence outcomes of assisted reproduction …”
Section: Introductionmentioning
confidence: 99%
“…However, one study revealed that AM could not predict male semen quality [50]. A recent meta-analysis demonstrated that increasing male BMI was associated with a significant reduction in clinical pregnancy rate and live birth rate in IVF cycles [16].…”
Section: Discussionmentioning
confidence: 99%
“…The WC, WHR, and WHtR have also been used for the assessment of obesity, which is a gradually predominant health condition in modern society [9]. The negative associations between obesity and male and female fertility are well documented [10][11][12][13][14][15][16]. However, the majority of previous studies have used the BMI to estimate overall adiposity, without taking body fat distribution into account.…”
Section: Introductionmentioning
confidence: 99%